Rolling deformation method for improving mechanical property of CoCrFeNiMo0.35 high-entropy alloy
Through precisely controlled hot rolling process, the CoCrFeNiMo0.35 high-entropy alloy is subjected to multiple-pass rolling and water quenching treatment, which solves the problems of low alloy strength and casting defects, significantly improves its mechanical properties and broadens its engineering application potential.
Patent Information
- Application Number
- CN202411566207.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-11
AI Technical Summary
CoCrFeNiMo0.35 high-entropy alloy has low strength and pores and inclusion defects in castings, which affects its mechanical properties and industrial applications.
By accurately controlling the insulation temperature, rolling speed and rolling pressure of rolling deformation, the CoCrFeNiMo0.35 high-entropy alloy is subjected to multi-pass rolling and water quenching to refine the alloy grains and eliminate the structure defect.
The yield strength and tensile strength of CoCrFeNiMo0.35 high-entropy alloy are significantly improved, with the yield strength up to 817.8MPa and the tensile strength reaching 891.7MPa, which is 125% and 43.7% higher than that of cast alloys.
Smart Images

Figure CN119411035A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of alloy materials, in particular to an improved CoCrFeNiMo 0.35 Rolling deformation method for mechanical properties of high entropy alloys. Background Art
[0002] As a new type of material, high entropy alloys have unique physical and chemical properties such as high strength, high plasticity, good radiation and corrosion resistance, biocompatibility and wear resistance compared to traditional alloys. They show great application potential in many fields such as aerospace, nuclear industry, and biomedicine.
[0003] The microstructure of high entropy alloys is usually composed of solid solution phases. According to the crystal structure, they can be divided into body-centered cubic (BCC), face-centered cubic (FCC) and hexagonal close-packed (HCP) structures. Among them, CoCrFeNi high entropy alloys with FCC crystal structure show excellent tensile ductility and fracture toughness at room temperature and low temperature, but the strength of CoCrFeNi alloys is relatively low, which is not enough to meet the requirements of engineering applications. At present, there have been many research reports to try to solve the problem of low strength. Studies have found that alloying is an effective strengthening method. Among them, Mo elements can form hard metal interphases with Co, Cr, Fe, and Ni elements due to their large atomic size, and can also cause serious lattice distortion, so that the strength of CoCrFeNi alloys with FCC structure can be significantly improved, thus developing CoCrFeNiMo high entropy alloys. Although CoCrFeNiMo high entropy alloys have good high temperature strength, their alloy castings often have many defects, such as pores and inclusions, which seriously affect their mechanical properties and industrial applications. At present, the above-mentioned problems are encountered in the research process of high entropy alloys. Many scholars use rolling technology to refine alloy grains, eliminate structural defects, etc., so as to improve the comprehensive performance of castings.
[0004] Compared with other rolling processes, hot rolling has the characteristics of low deformation resistance, elimination of defects such as pores, and dense organization. It can transform the cast structure into a deformed structure, greatly improving the comprehensive properties of the alloy. For example, Wu et al. used hot rolling to study FeNiMnAlCr alloy and found that hot rolling can significantly improve the mechanical properties of FeNiMnAlCr alloy (Wu M, Yang C, Kuijer M, Baker I. Enhanced mechanical properties of carbon-dopedFeNiMnAlCr high entropy alloy via hot-rolling. Mater Char 2019; 158: 109983). Saha et al. reported the effect of severe hot rolling on the microstructure and properties of CoCrFeMnNi HEA. After hot rolling at 750°C, the microstructure of the alloy was fully recrystallized, the grains were refined, and the alloy showed excellent strength and plasticity (Saha J, Ummethala G, Malladi SRK, Bhattacharjee PP. Severe warm-rolling mediated microstructure and texture of equiatomic CoCrFeMnNi high entropy alloy: A comparison with cold-rolling. Intermetallics 2021; 129: 107029). In addition, Wang et al. studied the effect of severe hot rolling on the microstructure and properties of CoCrFeNiMo in the temperature range of 700-1100°C. 0.2 HEA conducted hot compression experiments to study the deformation behavior of the alloy and clarified the organizational change law of Mo element leading to σ phase precipitation and promoting grain refinement (Wang JW, Liu Y, Liu B, Wang Y, Cao YK, Li TC, et al. Flow behavior and microstructure of powder metallurgical CrFeCoNiMo 0.2 Highentropy alloy during high temperature deformation.Mater Sci Eng 2017;689:233-42), but the above study did not clarify the relationship between the structure and properties of the cast alloy with Mo content between 0.3 and 0.4, nor did it study the effect of hot rolling process with different reduction on its structure and properties. 0.35 The hot rolling process of high entropy alloys and its influence on the deformed structure and mechanical properties have not been attempted or reported so far.
[0005] In summary, the present invention proposes a method for improving CoCrFeNiMo 0.35 Rolling deformation method for mechanical properties of high entropy alloys. Summary of the invention
[0006] The purpose of the present invention is to provide a method for improving CoCrFeNiMo 0.35 The rolling deformation method of high entropy alloy mechanical properties successfully improved CoCrFeNiMo by precisely controlling the holding temperature before rolling and the rolling speed and rolling reduction during rolling. 0.35 Mechanical properties of high entropy alloys. Compared with the alloys before rolling deformation, the alloys obtained by the technology of the present invention exhibit higher tensile strength.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] The invention proposes a method for improving CoCrFeNiMo 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy comprises the following steps:
[0009] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0010] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain rectangular samples.
[0011] (3) placing the rectangular sample described in step (2) in a heat treatment furnace for heat preservation treatment.
[0012] (4) The alloy sample after the heat preservation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. In this process, after each rolling pass, the alloy is returned to the heat treatment furnace for heat preservation treatment again, and the next rolling pass is carried out after the heat preservation treatment is completed.
[0013] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo after rolling deformation. 0.35 High entropy alloy.
[0014] Preferably, the insulation temperature in step (3) is 900° C. and the insulation time is 30 min.
[0015] Preferably, the rolling speed used in the rolling deformation process in step (4) is 0.1 m / s, and the rolling reduction per pass is 5%.
[0016] Preferably, the insulation temperature of the insulation treatment in step (4) is 900° C. and the insulation time is 10 min.
[0017] Compared with the prior art, the present invention has the following beneficial effects:
[0018] The hot rolling deformation technology proposed in the present invention can make CoCrFeNiMo 0.35 The microstructure of the high-entropy alloy is refined, and at the same time, the defects of the cast sample such as pores can be eliminated, which makes the alloy microstructure denser. Moreover, with the increase of rolling reduction, the grains are further refined. This is the first major factor leading to the improvement of the mechanical properties of the alloy. In addition, during the hot rolling deformation process, the alloy grains are stretched into a flat shape along the rolling direction. With the increase of rolling reduction, the volume fraction of the σ phase increases. The σ phase is a common hard phase in high-entropy alloys, which will also promote the improvement of the alloy strength.
[0019] Finally, CoCrFeNiMo 0.35 The yield strength and tensile strength of the high-entropy alloy have been significantly improved, with the yield strength reaching up to 817.8MPa and the tensile strength reaching 891.7MPa. Compared with the cast alloy, the yield strength and tensile strength have increased by 125% and 43.7% respectively.
[0020] In summary, the present invention precisely controls the hot rolling process to make CoCrFeNiMo 0.35 The microstructure of the high entropy alloy is refined and dense, the defects of the cast microstructure are eliminated, and the volume fraction of the σ phase in the alloy is increased, which ultimately improves the CoCrFeNiMo 0.35 The yield strength and tensile strength of high entropy alloys. The significant improvement of the mechanical properties of the alloy is of great significance for overcoming the shortcomings of the mechanical properties of the alloy and broadening its engineering application potential and demand. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is cast CoCrFeNiMo 0.35 XRD patterns of high entropy alloys;
[0022] Figure 2 It is cast CoCrFeNiMo 0.35 Surface SEM images and element distribution of high entropy alloys: (a) Typical microstructure; (b) Element distribution in the yellow frame area of (a);
[0023] Figure 3 It is CoCrFeNiMo after hot rolling deformation0.35 XRD patterns of high entropy alloys;
[0024] Figure 4 CoCrFeNiMo under different hot rolling reduction 0.35 SEM photos of the RD-TD (RD represents rolling direction, TD represents transverse direction) surface of high entropy alloy: (a, a-1) 10% reduction; (b, b-1) 20% reduction; (c, c-1) 30% reduction; (d, d-1) 40% reduction; (e, e-1) 50% reduction;
[0025] Figure 5 CoCrFeNiMo under different hot rolling reduction 0.35 SEM images of the surface of high entropy alloy RD-ND (RD represents rolling direction, ND represents normal direction): (a, a-1) 10% reduction; (b, b-1) 20% reduction; (c, c-1) 30% reduction; (d, d-1) 40% reduction; (e, e-1) 50% reduction;
[0026] Figure 6 It is CoCrFeNiMo after casting and hot rolling deformation 0.35 Phase distribution diagram of high entropy alloy: (a) as-cast; (b) 10% reduction; (c) 30% reduction; (d) 50% reduction;
[0027] Figure 7 It is CoCrFeNiMo after casting and hot rolling deformation 0.35 Tensile stress-strain curves of high entropy alloys. DETAILED DESCRIPTION
[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] The present invention proposes a method for improving CoCrFeNiMo 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy comprises the following steps:
[0030] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0031] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain a rectangular sample with a size of 60 mm × 30 mm × 15 mm.
[0032] (3) The rectangular sample of step (2) is placed in a heat treatment furnace for heat preservation treatment at a temperature of 900° C. for 30 min.
[0033] (4) The alloy sample after the heat preservation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. In this process, after each rolling pass, the alloy is returned to the heat treatment furnace for heat preservation treatment again, and the next rolling pass is carried out after the heat preservation treatment is completed.
[0034] In this step, the rolling deformation process preferably has a rolling speed of 0.1 m / s and a rolling reduction of 5% per pass.
[0035] In this step, the insulation temperature of the insulation treatment is 900° C. and the insulation time is 10 minutes.
[0036] In this step, the preferred rolling reduction is 10%, 20%, 30%, 40%, or 50%.
[0037] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo after rolling deformation. 0.35 High entropy alloy.
[0038] The cast and hot-rolled CoCrFeNiMo 0.35 High entropy alloy, mechanical properties test, the test method is as follows:
[0039] The cast and hot-rolled alloys were subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum experimental load was 100 kN, and the tensile rate was 0.5 mm / min.
[0040] The present invention will be described below by specific examples, and it will be appreciated by those skilled in the art that the following specific examples are only for illustrative purposes, and do not limit the scope of the present invention in any way. In addition, in the following examples, unless otherwise specified, the reagents and equipment used are all commercially available. If in the following examples, specific treatment conditions and treatment methods are not clearly described, then conditions and methods known in the art can be used to process.
[0041] Comparative Example 1
[0042] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0043] (2) The cast alloy was subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.
[0044] Example 1
[0045] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0046] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain a rectangular sample with a size of 60 mm × 30 mm × 15 mm.
[0047] (3) The rectangular sample of step (2) is placed in a heat treatment furnace for heat preservation treatment at a temperature of 900° C. for 30 min.
[0048] (4) The alloy sample after the insulation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. The rolling speed selected in this process is 0.1m / s, and the rolling reduction in each pass is 5%. At the same time, after each rolling pass, the alloy is returned to the heat treatment furnace for insulation treatment at 900°C for 10 minutes, and then rolled again. After the last rolling pass, the rolling reduction of the alloy is 10%.
[0049] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo with a rolling reduction of 10% 0.35 High entropy alloy.
[0050] (6) The CoCrFeNiMo 0.35 High entropy alloy was subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.
[0051] Example 2
[0052] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0053] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain a rectangular sample with a size of 60 mm × 30 mm × 15 mm.
[0054] (3) The rectangular sample of step (2) is placed in a heat treatment furnace for heat preservation treatment at a temperature of 900° C. for 30 min.
[0055] (4) The alloy sample after the insulation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. The rolling speed selected in this process is 0.1m / s, and the rolling reduction in each pass is 5%. At the same time, after each rolling pass, the alloy is returned to the heat treatment furnace for insulation treatment at 900°C for 10 minutes, and then rolled again. After the last rolling pass, the rolling reduction of the alloy is 20%.
[0056] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo with a rolling reduction of 20% 0.35 High entropy alloy.
[0057] (6) The CoCrFeNiMo 0.35 High entropy alloy was subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.
[0058] Example 3
[0059] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0060] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain a rectangular sample with a size of 60 mm × 30 mm × 15 mm.
[0061] (3) The rectangular sample of step (2) is placed in a heat treatment furnace for heat preservation treatment at a temperature of 900° C. for 30 min.
[0062] (4) The alloy sample after the insulation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. The rolling speed selected in this process is 0.1m / s, and the rolling reduction in each pass is 5%. At the same time, after each rolling pass, the alloy is returned to the heat treatment furnace for insulation treatment at 900°C for 10 minutes, and then rolled again. After the last rolling pass, the rolling reduction of the alloy is 30%.
[0063] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo with a rolling reduction of 30% 0.35 High entropy alloy.
[0064] (6) The CoCrFeNiMo 0.35 High entropy alloy was subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.
[0065] Example 4
[0066] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0067] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain a rectangular sample with a size of 60 mm × 30 mm × 15 mm.
[0068] (3) The rectangular sample of step (2) is placed in a heat treatment furnace for heat preservation treatment at a temperature of 900° C. for 30 min.
[0069] (4) The alloy sample after the insulation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. The rolling speed selected in this process is 0.1m / s, and the rolling reduction in each pass is 5%. At the same time, after each rolling pass, the alloy is returned to the heat treatment furnace for insulation treatment at 900°C for 10 minutes, and then rolled again. After the last rolling pass, the rolling reduction of the alloy is 40%.
[0070] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo with a rolling reduction of 40% 0.35 High entropy alloy.
[0071] (6) The CoCrFeNiMo 0.35 High entropy alloy was subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.
[0072] Example 5
[0073] (1) Co, Cr, Fe, Ni, and Mo metal elements with a purity of 99.95-99.99% are selected as raw materials, weighed and proportioned according to a molar ratio of 1:1:1:1:0.35, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated for no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingot.
[0074] (2) The CoCrFeNiMo 0.35 The alloy ingot was wire cut to obtain a rectangular sample with a size of 60 mm × 30 mm × 15 mm.
[0075] (3) The rectangular sample of step (2) is placed in a heat treatment furnace for heat preservation treatment at a temperature of 900° C. for 30 min.
[0076] (4) The alloy sample after the insulation treatment in step (3) is subjected to multiple rolling passes, and the rolling direction is along the length direction of the alloy sample. The rolling speed selected in this process is 0.1m / s, and the rolling reduction in each pass is 5%. At the same time, after each rolling pass, the alloy is returned to the heat treatment furnace for insulation treatment at 900°C for 10 minutes, and then rolled again. After the last rolling pass, the rolling reduction of the alloy is 50%.
[0077] (5) The alloy sample after rolling in step (4) is immediately subjected to water quenching treatment to obtain CoCrFeNiMo with a rolling reduction of 50% 0.35 High entropy alloy.
[0078] (6) The CoCrFeNiMo 0.35 High entropy alloy was subjected to electric spark cutting to obtain tensile specimens, which were then subjected to tensile tests using a universal mechanical testing machine. During all tensile tests, an extensometer (Epsilon 3442) with a gauge length of 10 mm was used, the maximum load was 100 kN, and the tensile rate was 0.5 mm / min.
[0079] The corresponding CoCrFeNiMo under different rolling reduction of the present invention 0.35 The room temperature tensile engineering stress-strain curve of high entropy alloy is as follows: Figure 7 As shown. It can be seen that as the rolling reduction increases from 10% to 50%, the yield strength and tensile strength of the alloy increase significantly. When the rolling reduction is 50%, the rolled CoCrFeNiMo 0.35 High entropy alloys have the highest strength.
[0080] The reasons for the change of mechanical properties are Figure 4 and Figure 5 The alloy structure shown in the figure is explained with the change of rolling reduction. Figure 4 and Figure 5 It can be seen that during the hot rolling process, as the reduction increases, the structure of the alloy changes from a typical dendritic structure to a dendritic structure roughly distributed along the rolling direction. Figure 5 The change trend of the longitudinal section is more obvious, and the structure is obviously refined. The number of grain boundaries in the alloy will increase, and the hindering effect of grain boundaries on dislocation movement will be enhanced, which is beneficial to the improvement of alloy strength. The σ between dendrites is a common hard and brittle phase under high temperature conditions and is not easy to deform. From the enlarged picture in the upper right corner, we can see that with the continuous increase in the amount of reduction, the σ phase will be broken under the action of stress, which makes the volume fraction of the σ phase increase, thereby improving the strength of the alloy. Figure 3 is the XRD diagram of the rolled alloy. The results show that the phase composition does not change after rolling. Figure 1The as-cast results are consistent, both consisting of FCC phase and σ phase. Figure 2 The surface scanning results show that the four elements Co, Cr, Fe, and Ni are evenly distributed in the dendrites and between the dendrites, while the σ phase distributed between the dendrites is enriched with Cr and Mo elements. Figure 6 The phase distribution diagram of the alloy shows that after hot rolling at 900℃, the phase content of the alloy changes with the reduction, but the phase composition remains unchanged. The alloy is still composed of FCC phase and σ phase. Under the hot rolling condition of 900℃, the high temperature accelerates the diffusion rate of alloy elements. With the increase of rolling reduction, the proportion of σ phase gradually increases from 2.5% to 10.9%. Rolling promotes the formation of σ phase. The deformation method of rolling flattens and refines the structure, and the volume fraction of σ phase increases, thereby improving the mechanical properties of the alloy.
[0081] In Example 5, when the rolling reduction is 50%, the hot-rolled CoCrFeNiMo 0.35 The room temperature tensile properties of high entropy alloys are the best. The yield strength reaches 817.8MPa and the tensile strength reaches 891.7MPa. These data show that rolling deformation can greatly improve the CoCrFeNiMo 0.35 Strength of high entropy alloys.
[0082] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered exemplary and non-limiting in all respects, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations falling within the meaning and scope of the equivalent elements of the claims be included in the invention. Any reference numeral in a claim should not be considered as limiting the claim to which it relates.
[0083] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.
Claims
1. A method to improve CoCrFeNiMo 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy, characterized in that: The following steps are involved: S1, Co, Cr, Fe, Ni, Mo metal single substances are used as raw materials, weighed and proportioned, and placed in an arc melting furnace for melting. To ensure the uniformity of the composition, the melting process is repeated no less than 5 times, and naturally cooled until solidified to obtain CoCrFeNiMo 0.35 Alloy ingots; S2, the CoCrFeNiMo in step S1 0.35 The alloy ingot was wire cut to obtain a rectangular sample; S3, placing the rectangular parallelepiped sample described in step S2 in a heat treatment furnace for heat preservation treatment; S4, the alloy sample after the heat preservation treatment in step S3 is subjected to multiple rolling, and the rolling direction is along the length direction of the alloy sample. In this process, the alloy is put back into the heat treatment furnace for heat preservation treatment after each rolling, and the next rolling is carried out after the heat preservation treatment is completed; S5, immediately subjecting the alloy sample after rolling in step S4 to water quenching to obtain CoCrFeNiMo after rolling deformation. 0.35 High entropy alloy.
2. The CoCrFeNiMo catalyst according to claim 1 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy, characterized in that: In the step S1, the purity of the metal elements Co, Cr, Fe, Ni and Mo is 99.95-99.99%.
3. The CoCrFeNiMo improved according to any one of claims 1 or 2 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy, characterized in that: In the step S1, the metal elements Co, Cr, Fe, Ni and Mo are weighed and proportioned according to a molar ratio of 1:1:1:1:0.
35.
4. The CoCrFeNiMo catalyst according to claim 1 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy, characterized in that: In step S3, the insulation temperature is 900° C. and the insulation time is 30 minutes.
5. The CoCrFeNiMo improved according to claim 1 0.35 A rolling deformation method for improving the mechanical properties of a high entropy alloy, characterized in that: In the step S4, the rolling speed used in the rolling deformation process is 0.1 m / s, and the rolling reduction per pass is 5%.
6. The CoCrFeNiMo catalyst according to claim 1 0.35 Rolling changes of mechanical properties of high entropy alloys A method, characterized in that: In step S4, the heat preservation temperature of the heat preservation treatment is 900° C. The insulation time is 10 minutes.
Citation Information
Patent Citations
High-strength and high-plasticity high-entropy alloy and preparation method thereof
CN111961893A
Hot rolling process method for improving comprehensive mechanical properties of structural eutectic high-entropy alloy
CN117086105A
Cited By
Microstructure and performance optimized TiNiCuNb alloy and preparation method thereof
CN120193181A